A Secure and Fair Joint E-Lottery Protocol - Chin-Ling Chen; Yuan-Hao Liao; Woei-Jiunn Tsaur (The Scientific World Journal)
The attractive huge prize causes people to adore lotteries. Due to the very small probability of winning prizes, the players can enhance their probability of winning by using the method of joint purchase. In spite of many lottery schemes having been proposed, most e-lottery schemes focus on the players’ privacy or computation overhead rather than support a joint purchase protocol on the Internet. In this paper, we use the multisignature and verifiable random function to construct a secure and fair joint e-lottery scheme. The players can check the lottery integrity, and the winning numbers can be verified publicly.